THE DIDACTIC IMPORTANCE OF CREATIVITY AND SKILLS IN STUDENT ACTIVITIES - Najiyeva, S.N. (SCIENCE and SOCIETY, 2020)
The article studies creative process, creating comfortable environment for gifted students, inventing a new things, new models, creating a real waster pieces of art, and also there presents some changes into ready objects, independent decisions, drawing personal conclusions.